Nehru Mama, oru yaanai anuppuveergala நேரு மாமா, ஒரு யானையை அனுப்புவீர்களா! - Cariapa, Devika,Gade, Satwik,Jeeva Raghunath (Tulika, 2021)
This exuberant picture book introduces first Prime Minister of India to children through his unique elephant diplomacy, taking readers across land and sea to tell how elephants became big gifts of India to the world.
Children's story. - Translated from English. - Translation of: Uncle Nehru, please send an elephant!
Keywords: Elephants; Juvenile fiction.; Elephants; Pictorial works; Juvenile fiction.; Children's stories; Indic (English); Translations into Tamil.; Children's stories; Indic (English); Pictorial works; Translations into Tamil.